ROOT SYSTEM AND DRY MASS OF WINTER WHEAT UNDER PROVOKING CONDITIONS “ZASUSHNIK” - E. V. Ionova; V. L. Gaze; V. M. Sharova; Е. I. Nekrasov (Зерновое хозяйство России)
The article gives the effect of water stress on formation of root system and overland parts of wheat under provoking conditions “zasushnik” (vegetation experience). It has been established that at the beginning of the stress the mass of roots reduced a bit, but then the process of accumulation of root mass stabilized due to adaptation to water stress. Comparing winter wheat samples ‘Don 93’ and ‘488/07’, the root system of ‘Don 93’ is more adaptive to drought than that of the sample ‘488/07’. In the phase of milky ripeness of the grain, dry mass of roots of the variety ‘Don 93’ decreased on 3%, and dry mass of roots of the variety ‘488/07’ reduced on 32%. In the phase of waxy ripeness of the grain, the number of roots varied from 9 to 16 pieces (trial) and from 10 to 17 pieces (control). The data about response of the root system of the varieties and lines of winter wheat on water stress in various phases of organogenesis have been given. It has been determined that root system plays an essential part in the process of adaptation to drought among steppe crop varieties. The varieties ‘Kaprizyulya’, ‘Asket’, ‘Kazaka’, ‘Kapitan’ and ‘Lidiya’ have shown the highest level of adaptation to harsh, severe drought.